2020
DOI: 10.1186/s40779-020-00278-0
|View full text |Cite
|
Sign up to set email alerts
|

Quetiapine augmentation of prolonged exposure therapy in veterans with PTSD and a history of mild traumatic brain injury: design and methodology of a pilot study

Abstract: Background Selective serotonergic reuptake inhibitors (SSRIs) are first-line pharmacologic treatments for patients with posttraumatic stress disorder (PTSD), but must be given over extended period of time before the onset of action. The use of SSRIs in PTSD patients with mild traumatic brain injury (mTBI) is problematic since SSRIs could exacerbate post-concussion syndrome (PCS) symptoms. VA/DOD guidelines identify trauma-focused psychotherapy as the best evidence-based treatment for PTSD, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…To tackle the negative effects of sleep deprivation or poor sleep quality on the mental health well-being of soldiers, Harrison et al [23] studied the chronotype profile of U.S. sailors, and suggested aligning military schedules with endogenous circadian rhythms to optimise performance. On the other hand, Baig et al [24] found that quetiapine monotherapy can increase engagement in trauma-focused psychotherapy, given that fluoxetine, the alternative pharmacologic treatment for PTSD, has an extended onset of action and can exacerbate post-concussion syndrome in mild TBI. Despite military psychiatry being an established field, there leaves much more knowledge to be discovered in this ever-evolving specialty, which is only made possible with continued research.…”
Section: Military Psychiatrymentioning
confidence: 99%
“…To tackle the negative effects of sleep deprivation or poor sleep quality on the mental health well-being of soldiers, Harrison et al [23] studied the chronotype profile of U.S. sailors, and suggested aligning military schedules with endogenous circadian rhythms to optimise performance. On the other hand, Baig et al [24] found that quetiapine monotherapy can increase engagement in trauma-focused psychotherapy, given that fluoxetine, the alternative pharmacologic treatment for PTSD, has an extended onset of action and can exacerbate post-concussion syndrome in mild TBI. Despite military psychiatry being an established field, there leaves much more knowledge to be discovered in this ever-evolving specialty, which is only made possible with continued research.…”
Section: Military Psychiatrymentioning
confidence: 99%
“…Pharmacological and physical therapies for TBI remain a research focus. A 2020 study suggested that quetiapine augmentation of prolonged exposure therapy may be beneficial to veterans suffering from TBI and PTSD, but the effectiveness of the treatment has yet to be proven [139]. In a meta-analysis involving 7 randomized controlled trials testing the TBI-treating effect of erythropoietin (EPO), no statistically significant results were found in neurological function improvement and acute hospitalization rate reduction after 6 months; however, the EPO intervention group had a more significant survival benefit than the saline placebo group [140].…”
Section: Tentative Treatmentsmentioning
confidence: 99%